1993
DOI: 10.1161/01.cir.88.6.2548
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after the onset of coronary heart disease. An investigation of differences in outcome between the sexes according to initial coronary disease presentation.

Abstract: Women fare at least as poorly as men after recognized myocardial infarction, whereas women have a more favorable outlook than men after the onset of angina or unrecognized myocardial infarction. The favorable outcome in women after angina and unrecognized myocardial infarction is due, in part, to greater misclassification of these coronary events in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
9

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(87 citation statements)
references
References 31 publications
8
70
0
9
Order By: Relevance
“…EKG abnormalities that can be mistaken for MI but are not caused by coronary disease are more often seen in women than in men, possibly caused by difficulties in correctly placing the electrodes due to breast tissue. 32 Because of this possible nondifferential misclassification of our determinant, dilution of the effect might have occurred and therefore the true effect may have been missed in women in our data set. Such misclassification might also explain the higher prevalence of unrecognized MI among women than men.…”
Section: Discussionmentioning
confidence: 95%
“…EKG abnormalities that can be mistaken for MI but are not caused by coronary disease are more often seen in women than in men, possibly caused by difficulties in correctly placing the electrodes due to breast tissue. 32 Because of this possible nondifferential misclassification of our determinant, dilution of the effect might have occurred and therefore the true effect may have been missed in women in our data set. Such misclassification might also explain the higher prevalence of unrecognized MI among women than men.…”
Section: Discussionmentioning
confidence: 95%
“…The risk for heart disease or subclinical or clinical disease exists even as patients enter dialysis treatment. In the United States Renal Data System (USRDS) Wave 2 study, for example, the prevalence of ischemic heart disease and cardiac failure was approximately 40% before renal replacement, much higher than the 2 to 26% reported in the general population (3). In a Canadian study, baseline echocardiography identified 74% of patients entering first-time dialysis treatment with left ventricular (LV) hypertrophy (4).…”
Section: Epidemiologymentioning
confidence: 99%
“…Stable angina or chest pain is commonly the initial presentation of coronary disease, particularly in women (33) and may precede myocardial infarction by years. Diagnosis is notoriously difficult, and increasingly it is observed that there is an appreciable risk of subsequent coronary events(34) among patients with "non-cardiac" chest pain (35), nonobstructed angiograms(36) and admissions with "chest pain" without further diagnosis.…”
Section: Discussionmentioning
confidence: 99%